Understanding resilience and coping in a digitally transformed educational environment during COVID-19. Issue 2 (7th February 2023) - Alhawsawi, Hajeej; Alhawsawi, Sajjadllah; Sadeck, Osman
ABSTRACT: The lasting effects of COVID-19 on education are not yet fully understood. However, many studies have reported on how educationalists and students have responded to the transition from the traditional classrooms to an emergency remote learning and teaching. Prominent researchers in the field strongly argue that teachers' contexts exert a critical role in influencing teachers' resilience. There are fewer studies that targeted resilience during COVID-19. Research into resilience in education is relatively new, approximately 10–15 years old. A global compilation of emergency remote education was conducted in 2020. This paper draws on the 2020 research compilation, and further shares its findings through a resilience lens. The study was conducted at a Saudi Arabian university and employed a mixed-method research approach. This paper reports on the qualitative findings only. Findings from this study have shown that gender inequity may be the contributing factor that female educators experienced. They experienced challenges in terms of personal resources and internal processes; however, despite these setbacks, teachers have adapted and coped regardless of material challenges.